The body keeps the score : Brain, mind, and body in the healing of trauma - Van der Kolk, Bessel A. (Penguin Books, 2014)
This groundbreaking book explores how trauma reshapes both the body and the brain, affecting emotions, memory, and behavior. Dr. Bessel van der Kolk, a leading expert in trauma, explains how traumatic experiences can be stored in the body and continue to impact mental and physical health. The book examines traditional and innovative treatments-including talk therapy, EMDR, yoga, and neurofeedback-that help survivors heal by reconnecting with their bodies and reclaiming a sense of safety and control.